A Social Experience, Social Entrepreneurship Self-Efficacy, and Self-Esteem on Therapist BE (Bio-Electric): SMEs in Healthcare Case: - - Tsabita Khwarazmita; Agus Hermawan; Naswan Suharsono (International Journal of Economics, Business and Innovation Research, 2023)
This research uses traditional cross-section research to find out the impact of social experience on social self-efficacy, self-esteem, and social entrepreneurial intentions, as well as the mediation of social self-efficacy and self-esteem. The framework mentioned above is linked to micro-sized social entrepreneurship in the field of health alternatives in Indonesia. The alternative health appointment is based on the concept of solving Indonesian social problems related to harmony and equitable distribution of health where comprehensive acting as a sociopreneur. In this research, 68 respondents were experimented quantitatively with the support of SmartPLS 4.0 software and analysis. Through this, it was found from this research that the impact of social experiences was positive and significant on social entrepreneurial self-efficacy, self-esteem, and social entrepreneurial intentions. Likewise, the mediating role of self-efficacy and self-esteem in influencing social entrepreneurial intentions. Furthermore, this research describes the conditions of social entrepreneurship associated with health alternatives in Indonesia by counting empirical and practical depictions. These depictions should be able to stimulate research on social entrepreneurship in Indonesia and extend the practice of social entrepreneurship concepts in Indonesia.